2019
DOI: 10.1371/journal.pone.0211826
|View full text |Cite|
|
Sign up to set email alerts
|

Blue light-dependent human magnetoreception in geomagnetic food orientation

Abstract: The Earth’s geomagnetic field (GMF) is known to influence magnetoreceptive creatures, from bacteria to mammals as a sensory cue or a physiological modulator, despite it is largely thought that humans cannot sense the GMF. Here, we show that humans sense the GMF to orient their direction toward food in a self-rotatory chair experiment. Starved men, but not women, significantly oriented toward the ambient/modulated magnetic north or east, directions which had been previously food-associated, without any other he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…It is widely accepted that the Earth’s static magnetic field is not sensed by humans, while alternating magnetic fields, such as power frequency fields 26 and pulsed fields 27 , can have adverse health effects and therapeutic applications, respectively. Following previous controversial reports 28 30 , two recent studies, using different experimental approaches, support the existence of GMF responses in humans 31 , 32 with a sharp contrast. In a rotary chair experiment, starved men but not women were able to orient in a blue-light-dependent manner towards a particular magnetic direction that had previously been associated with food in the ambient GMF 31 .…”
Section: Introductionmentioning
confidence: 70%
“…It is widely accepted that the Earth’s static magnetic field is not sensed by humans, while alternating magnetic fields, such as power frequency fields 26 and pulsed fields 27 , can have adverse health effects and therapeutic applications, respectively. Following previous controversial reports 28 30 , two recent studies, using different experimental approaches, support the existence of GMF responses in humans 31 , 32 with a sharp contrast. In a rotary chair experiment, starved men but not women were able to orient in a blue-light-dependent manner towards a particular magnetic direction that had previously been associated with food in the ambient GMF 31 .…”
Section: Introductionmentioning
confidence: 70%
“…The authors reported that food-deprived males, but not females, significantly preferred the magnetic direction that had previously been food-associated. Without food deprivation, neither gender was able to establish such an association (Chae et al, 2019). Gender bias in magnetic orientation the authors cautiously interpret as result of stronger selection for orientation abilities in prehistoric male humans who were dominantly responsible for gathering or hunting for food.…”
Section: Behavioral Studies In Humansmentioning
confidence: 88%
“…In a recent study, participants (20 males aged 19-33 years and 21 females aged 19-23 year) were asked to point by hand towards the magnetic North, which may have been rotated in respect to the geographic North by magnetic coils (Chae et al, 2019). Each participant underwent 20 tests in a rotating chair, the results of which were averaged and the mean used in the second-order analysis.…”
Section: Behavioral Studies In Humansmentioning
confidence: 99%
See 2 more Smart Citations